A review of policy debates around learning in the post-2015 education and development agenda. (January 2015) - Winthrop, Rebecca; Anderson, Kate; Cruzalegui, Inés
Highlights: The learning crisis and the growing funding gap in education suggest that equitable access and learning are still global pending challenges, despite nearly 25 years of global education goals. Education stakeholders have come to general agreement on a set of targets to inform the post-2015 development and education agendas. Regardless of post-2015 decisions, efforts should focus on building robust systems for measuring learning and making better use of data to improve learning outcomes. Abstract: Currently, ministers of education and education practitioners around the world are bemoaning the disproportionately shrinking development aid budgets in the education sector at the same time as member states of the United Nations debate whether and if so how to include education as a global development priority in the post-2015 agenda. What role has an increasing focus on learning played in the policy debates of the post-2015 development agenda? The article will review the arguments and evidence shaping high-level policy-makers' discussion on education as well as the process by which the education community has entered into a conversation about how to measure learning at the global level. In particular, the debates carried out within the broad consultation process of the Learning Metrics Task Force are examined.